Sondeo de habilidades preacademicas en niños y niñas mexicanos de estrato socioeconomico bajo - Guevara Benitez, Yolanda; Flores, Silvia Macotela (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
One hundred children beginning elementary education were studied in order to determine the linguistic and pre-academic skills which children belonging to a low socioeconomic status bring when entering first grade. Fifty children had attended preschool and 50 had not. All children were evaluated with the Pre-Reading Skills Assessment Instrument (PRSAJ: Vega, 1991) and the School Learning Aptitude Battery (SLAB; De la Cruz. 1989). Differences between groups were found only in the latter instrument. Scores in both instruments resulted particularly low for the entire sample. This finding is discussed in terms of the role of preschool education for children belonging to a low socioeconomic status.